Thermodynamic and combustion characteristics of ultra-high performance engines for motorsport applications - Le Roux de Bretagne, Olivier (Cranfield University, 2023)
Using steady-state and transient one-dimensional gas dynamic engine models developed with AVL Boost™, critical assessment of the performance characteristics of the current 2014+ Formula One™ engine and of the future 2026 Formula One™ Power Unit are investigated. For the 2014+ regulations, a Digital Twin, aiming at replicating the trends of the real engine despite a lack of component-level-detail data, is created and used to scientifically explain how this engine achieves 50+% brake fuel conversion efficiency and to rank the contribution of each enabling technologies (high compression ratio, lean combustion, passive pre-chamber, direct injection, asymmetric valve profiles, MGU-H and waste gates used as pressure-relief valves). The impact of the 2026 Formula One™ Power Unit regulations on engine performance is investigated and highlights that the reduction in fuel flow will not only result in the obvious reduction in power output but also in in-cylinder pressure which introduces opportunities for enhanced combustion process and higher air/fuel ratios. Nevertheless, with the high MGU-K power, both the 2014+ and 2026 Power Units are predicted to have similar peak output power despite an advantage at low speed for the 2026 regulations thanks to the capacity of electric motor to produce torque at low speed. Using transient simulations, the impact of the removal of the MGU-H in the 2026 regulations is assessed and an anti-lag solution using the MGU-K called torque consuming is investigated. It is demonstrated that always operating the engine at full load during acceleration phases and using the MGU-K to absorb the excess power compared to the power demand / to control the amount of power delivered to the wheels helps to reduce turbo lag, improve engine efficiency, and reduce the need for the MGU-K to torque fill, but at the expense of a higher fuel consumption.
Temple, Clive - Associate Supervisor
Keywords: Engine simulation; Digital Twin; AVL Boost™; Formula One™ Power Unit; Energy; Exergy; Turbo lag mitigation